The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1080/09362835.2013.771563
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Demand for Special Education Teachers: Indicators, Explanations, and Impacts

Abstract: After decades of growth, the number of special education teachers (SETs) has begun to decline. In 2009, U.S. schools employed 13% fewer SETs than in 2006. The number of annual new hires of SETs also dropped dramatically in some states. The onset of these declines predated the economic downturn of 2008 and resulted in part from a steady decline since 2005 in the number of students with disabilities (SWD) served. We consider factors that may be contributing to declining demand for SETs, among them the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 21 publications
1
28
0
1
Order By: Relevance
“…Rather, the shortage of qualified, prepared special educators available to work with students with specific disabilities, including emotional/behavioral disorders (EBDs), autism, and intellectual disabilities, as well as regional variations have been noted (Bowen & Klass, 1993; Lauritzen & Friedman, 1991, 1993; McLeskey, Tyler, & Flippin, 2004). More recently, evidence emerged that students with disabilities in high-poverty schools and districts were more likely to be taught by individuals with lesser qualifications and preparation (Fall & Billingsley, 2011; Mason-Williams, 2015), supporting what many researchers have long suggested: Teacher shortages and higher rates of attrition more often affect schools with high concentrations of poor and minority students and in exclusionary school settings (Boe, deBettencourt, Dewey, Rosenberg, Sindelar, & Leko, 2013; Brownell, Rosenberg, Sindelar, & Smith, 2004; McLeskey et al, 2004).…”
Section: Insufficient Supply and Attrition In Special Educationmentioning
confidence: 79%
See 1 more Smart Citation
“…Rather, the shortage of qualified, prepared special educators available to work with students with specific disabilities, including emotional/behavioral disorders (EBDs), autism, and intellectual disabilities, as well as regional variations have been noted (Bowen & Klass, 1993; Lauritzen & Friedman, 1991, 1993; McLeskey, Tyler, & Flippin, 2004). More recently, evidence emerged that students with disabilities in high-poverty schools and districts were more likely to be taught by individuals with lesser qualifications and preparation (Fall & Billingsley, 2011; Mason-Williams, 2015), supporting what many researchers have long suggested: Teacher shortages and higher rates of attrition more often affect schools with high concentrations of poor and minority students and in exclusionary school settings (Boe, deBettencourt, Dewey, Rosenberg, Sindelar, & Leko, 2013; Brownell, Rosenberg, Sindelar, & Smith, 2004; McLeskey et al, 2004).…”
Section: Insufficient Supply and Attrition In Special Educationmentioning
confidence: 79%
“…Moreover, the federal definition of HQT includes those individuals currently enrolled in a program leading to full certification, no matter how recently enrolled. These subtle nuances in reporting, as well as declines in the overall number of identified students (Boe et al, 2013), may suggest that shortages no longer plague special education. More likely, shortages and high rates of attrition impact certain schools or students with certain characteristics more so than others, leading to an uneven distribution of qualified, prepared special educators (Brownell et al, 2004; Fall & Billingsley, 2011; Mason-Williams, 2015; McLeskey et al, 2004).…”
Section: Insufficient Supply and Attrition In Special Educationmentioning
confidence: 99%
“…Focusing on the distribution of SETs is also important because policies aimed at solely increasing the supply of SETs will not be able to ensure that students with disabilities have access to qualified teachers (Boe et al, 2013). Studies examining the distribution of SETs have focused mainly on differences in SETs by school or district poverty levels.…”
Section: Distribution Of Setsmentioning
confidence: 99%
“…Although data available from the Data Accountability Center (www.ideadata.org) demonstrated that the proportion of SETs considered highly qualified increased to 94% by fall 2011 (U.S. Department of Education, 2012), questions remain regarding the extent to which schools rely on substitute teachers, the number of positions left unfilled, and the qualifications of indirect service providers who do not need to meet highly qualified teacher (HQT) requirements (Steinbrecher, McKeown, & Walther-Thomas, 2013). And although there may be an overall decline in demand for SETs, the uneven distribution of qualified, prepared SETs continues to hinder providing all students with disabilities an equitable education (Boe et al, 2013).…”
mentioning
confidence: 99%